The Assessment of SpondyloArthritis international Society classification criteria for peripheral spondyloarthritis and for spondyloarthritis in general. Issue 1 (24th November 2010) - Rudwaleit, M; van der Heijde, D; Landewé, R; Akkoc, N; Brandt, J; Chou, C T; Dougados, M; Huang, F; Gu, J; Kirazli, Y; Van den Bosch, F; Olivieri, I; et al.
Abstract : Objective: To evaluate new classification criteria for peripheral spondyloarthritis (SpA) in patients with SpA with peripheral manifestations only. Methods: In this Assessment of SpondyloArthritis international Society (ASAS) study, two prespecified sets of criteria were compared against the European Spondylarthropathy Study Group (ESSG) and Amor criteria in newly referred consecutive patients with undiagnosed peripheral arthritis, and/or enthesitis, and/or dactylitis that usually began before 45 years of age. The clinical diagnosis (SpA vs no SpA) made by the ASAS rheumatologist served as reference standard. Results: In all, 24 ASAS centres included 266 patients, with a final diagnosis of SpA being made in 66.2%. After adjustments a final set of criteria showed the best balance between sensitivity (77.8%) and specificity (82.9%): arthritis and/or enthesitis and/or dactylitis plus (A) one or more of the following parameters: psoriasis, inflammatory bowel disease, preceding infection, human leucocyte antigen B27, uveitis, sacroiliitis on imaging, or (B) two or more other parameters: arthritis, enthesitis, dactylitis, inflammatory back pain in the past, family history of SpA. The new criteria performed better than modified versions of the ESSG (sensitivity 62.5%, specificity 81.1%) and the Amor criteria (sensitivity 39.8%, specificity 97.8%), particularly regarding sensitivity. In the entire ASAS population of 975 patients the combined use of ASAS criteria for axial SpA and ASAS criteria for peripheral SpA also had a better balance (sensitivity 79.5%, specificity 83.3%) than the modified ESSG (sensitivity 79.1%, specificity 68.8%) and Amor criteria (sensitivity 67.5%, specificity 86.7%), respectively. Conclusions: The new ASAS classification criteria for peripheral SpA performed well in patients presenting with peripheral arthritis, enthesitis and/or dactylitis.